Effects of Ability and Effort Praise on Children’s Failure Attribution, Self-Handicapping, and Performance - Xing, Shufen; Gao, Xin; Jiang, Ying; Archer, Marc; Liu, Xia (Frontiers in Psychology, 2018)
Previous research has suggested that children praised for ability are more likely to attribute their failure to low-ability compared to those praised for effort. However, Self-worth Theory suggests that when individuals’ self-worth is threatened, protection strategies such as self-serving attributional strategy and self-handicapping would be adopted. In the perspective of Self-worth Theory, the current study investigated how ability and effort praise influenced children’s failure attribution, self-handicapping and their subsequent performance compared to simple informational feedback. Fifth graders (N = 103, average age = 11.2 years, SD = 0.71) were randomly assigned to three conditions of different feedbacks. Results revealed that children praised for ability were more likely to attribute their subsequent failure to non-ability factors and show more claimed and behavioral self-handicapping than children praised for effort and in control conditions. As the behavioral self-handicapping created actual obstacles, children praised for ability made significantly less improvement in the performance than those in other two groups. In addition, the current study showed that children praised for effort also adopted the claimed self-handicapping and defensive attributional strategy compared to those in no-praise condition. Results indicated that parents and teachers should haphazardly administer praises, especially ability praise. Implications for parents, teachers and the further researches, including the replication of this study in diverse cultural settings, conditions of effort praise and effects of other type of praises, are discussed.